2015
DOI: 10.1016/j.otsr.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Opening-wedge high tibial osteotomy with a secure bone allograft (Osteopure™) and locked plate fixation: Retrospective clinical and radiological evaluation of 69 knees after 7.5years follow-up

Abstract: IV, retrospective case-series study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Our findings therefore showed that a more neutral alignment was achieved for patients 6 months after upper partial fibulectomy. Two studies that used opening wedge high tibial osteotomy to treat medial compartment knee osteoarthritis reported mean increases of the HKA angle of 7.8 degrees and 8.6 degrees from a more varus to more neutral alignment. However, the baseline varus deformity of these subjects was 7 degrees and 6.7 degrees, respectively, which were greater than the mean baseline varus deformity (2 degrees) in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings therefore showed that a more neutral alignment was achieved for patients 6 months after upper partial fibulectomy. Two studies that used opening wedge high tibial osteotomy to treat medial compartment knee osteoarthritis reported mean increases of the HKA angle of 7.8 degrees and 8.6 degrees from a more varus to more neutral alignment. However, the baseline varus deformity of these subjects was 7 degrees and 6.7 degrees, respectively, which were greater than the mean baseline varus deformity (2 degrees) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies that used opening wedge high tibial osteotomy to treat medial compartment knee osteoarthritis reported mean increases of the HKA angle of 7.8 degrees and 8.6 degrees from a more varus to more neutral alignment. However, the baseline varus deformity of these subjects was 7 degrees and 6.7 degrees, respectively, which were greater than the mean baseline varus deformity (2 degrees) in our study. Thus, the range of HKA alteration for upper partial fibulectomy (mean increase of 1.80 degrees from a more varus to more neutral alignment) is less than high tibial osteotomy (HTO).…”
Section: Discussionmentioning
confidence: 99%
“…The best indications for HTO [12,[14][15][16][17] are: (1) The patients'age are less than 65 years old (female is less than 60 years old); (2) combined with humeral varus deformity, medial proximal tibial angle (MPTA) < 85°, kneecap varus angle (KVA) > 5° (3) knee joint activity is basically normal, flexion deformity should be less than 10° and force line deformity is less than 15°; (4) lateral cartilage and meniscus function are normal. HTO is an extra-articular surgery that can correct stress concentration in the joint and relieve pain by correcting patella varus outside the joint.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patient'the body should be carefully examined before surgery and lesions and pain sites should be confined on the medial side. Since combined lateral cartilage wear or lateral meniscus injury cannot be alleviated by HTO, and HTO may even aggravate this symptom after force line migration [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation